Idee wolności, równości i własności w prawie prywatnym (ze szczególnym uwzględnieniem umów o dostarczanie treści cyfrowych konsumentom) - Mańko, Rafał (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2016)
The article traces the realization of the concepts of liberty, equality, and property in the context of private law, with particular emphasis on the contracts for the supply of digital content. Reflections on each of the three aforementioned concepts consist of a general and specific part. The general part is historical and comparative in nature, while the specific part covers proposed rules governing contracts for the supply of digital content to consumers
Keywords: własność; równość; prawo prywatne; wolność; umowy o dostarczanie treści cyfrowych